2022
DOI: 10.1371/journal.pone.0274189
|View full text |Cite
|
Sign up to set email alerts
|

New strategies for characterizing genetic structure in wide-ranging, continuously distributed species: A Greater Sage-grouse case study

Abstract: Characterizing genetic structure across a species’ range is relevant for management and conservation as it can be used to define population boundaries and quantify connectivity. Wide-ranging species residing in continuously distributed habitat pose substantial challenges for the characterization of genetic structure as many analytical methods used are less effective when isolation by distance is an underlying biological pattern. Here, we illustrate strategies for overcoming these challenges using a species of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…This is consistent with previous genetic analyses for all three regions. The Bi‐State is a distinct though regionally relatively diverse population (Oh et al, 2019; Oyler‐McCance, Taylor, & Quinn, 2005; Oyler‐McCance et al, 2015) while Utah (Oyler‐McCance, Taylor, & Quinn, 2005; Oyler‐McCance et al, 2022) and Jackson (Oyler‐McCance et al, 2022; Schulwitz et al, 2014) have some evidence of being locally distinct and having relatively low genetic diversity. These findings are also consistent with previous reports of extensive habitat fragmentation (Schroeder et al, 2004; Schulwitz et al, 2014), and limited movement (Dahlgren et al, 2016) in all three regions when compared to the rest of the range.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous genetic analyses for all three regions. The Bi‐State is a distinct though regionally relatively diverse population (Oh et al, 2019; Oyler‐McCance, Taylor, & Quinn, 2005; Oyler‐McCance et al, 2015) while Utah (Oyler‐McCance, Taylor, & Quinn, 2005; Oyler‐McCance et al, 2022) and Jackson (Oyler‐McCance et al, 2022; Schulwitz et al, 2014) have some evidence of being locally distinct and having relatively low genetic diversity. These findings are also consistent with previous reports of extensive habitat fragmentation (Schroeder et al, 2004; Schulwitz et al, 2014), and limited movement (Dahlgren et al, 2016) in all three regions when compared to the rest of the range.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation by distance occurs within a continuously distributed population when movement of genes is spatially restricted (Hardy & Vekemans, 1999) and is an underlying pattern that likely challenged our ability to detect strong relationships between landscape variables and genetic differentiation (Oyler‐McCance et al, 2022). Our results were consistent with other landscape genetics studies that showed only incremental improvement in the amount of variation explained by final models when compared to a null expectation of isolation by distance (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Resistant kernels from models with paved roads as the only retained landscape variable (40,80,120,200 Isolation by distance occurs within a continuously distributed population when movement of genes is spatially restricted (Hardy & Vekemans, 1999) and is an underlying pattern that likely challenged our ability to detect strong relationships between landscape variables and genetic differentiation (Oyler-McCance et al, 2022).…”
Section: Maps Of Predicted Genetic Connectivitymentioning
confidence: 99%
“…The greater sage-grouse (Centrocercus urophasianus; hereafter, sage-grouse) is a species of conservation concern ranging across eleven western US states and two Canadian provinces. Sage-grouse populations are poised to benefit from the collection of greater than 16 000 genetic samples across their range [8,[10][11][12]. Sage-grouse populations vary substantially in population density and dispersal [13]; these two parameters are fundamentally influenced by connectivity, and both influence the genetic diversity of populations.…”
Section: Introductionmentioning
confidence: 99%
“…Data products and metadata are publicly available as follows. (i) FCM microsatellite and spatial data: https://doi.org/10.5066/F7RB73V0 [74]. (ii) NCM microsatellite, spatial and network attribute data: https://doi.org/ 10.5066/F73N22PN [75].…”
mentioning
confidence: 99%